2013
DOI: 10.3171/2013.6.focus13233
|View full text |Cite
|
Sign up to set email alerts
|

Dual occipital and supraorbital nerve stimulation for chronic migraine: a single-center experience, review of literature, and surgical considerations

Abstract: Occipital nerve stimulation (ONS) has been studied in a few clinical trials for the treatment of chronic migraine (CM) with failure to prove sufficient efficacy. To date, peripheral nerve stimulation for the treatment of primary headache is limited to off-label use only. The authors report their institutional experience in CM therapy with combined ONS and supraorbital nerve stimulation (SONS). Fourteen patients treated with dual ONS and SONS for CM were studied with follow-up ranging from 3 to 60 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 25 publications
1
37
0
2
Order By: Relevance
“…In general, these studies identified ONS as a promising potential treatment option but failed to provide definitive evidence of efficacy as one study was an underpowered feasibility study and the other two studies failed to meet their primary endpoints (despite meeting a number of secondary endpoints) [31][32][33]. Combined supraorbital nerve stimulation (SONS) and ONS has also been investigated in two open-label studies both of which have provided encouraging preliminary results [34,35]. Drawbacks to ONS and SONS include the fact that it is an invasive surgical procedure with a number of potential adverse events which include implant site infection, nontarget area sensory syndrome, implant site pain, and lead migration and fractures.…”
Section: O N S T I P a T I O N ) C O M P A R E D T O T H E Onabotulmentioning
confidence: 99%
“…In general, these studies identified ONS as a promising potential treatment option but failed to provide definitive evidence of efficacy as one study was an underpowered feasibility study and the other two studies failed to meet their primary endpoints (despite meeting a number of secondary endpoints) [31][32][33]. Combined supraorbital nerve stimulation (SONS) and ONS has also been investigated in two open-label studies both of which have provided encouraging preliminary results [34,35]. Drawbacks to ONS and SONS include the fact that it is an invasive surgical procedure with a number of potential adverse events which include implant site infection, nontarget area sensory syndrome, implant site pain, and lead migration and fractures.…”
Section: O N S T I P a T I O N ) C O M P A R E D T O T H E Onabotulmentioning
confidence: 99%
“…Occipital nerve stimulation is relatively safe, although long-term follow-up analysis in almost all studies has shown adverse events; in some studies, even 70% of patients reported a side effect; paresthesias being one of the most frequent one 29 ; as well as lead migration: 24%-58% of patients required at least one lead revision, 28,35,38 8.6% required hospitalization and 40.7% required repeated surgical intervention. 28,37 Battery depletion was reported in 64%, material infection in up to 20%.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…SON stimulation, [181][182][183][184] vagus nerve stimulation, [185][186][187][188][189][190]191,192 deep brain stimulation (DBS), [193][194][195][196][197][198][199][200] and spinal cord stimulation 201,202 have also been reported as potential treatment options for refractory and intractable chronic headache disorders.…”
Section: Neuromodulation Techniquesmentioning
confidence: 99%